Assessing the Effect of Weak and Strong Acids as Electrolytes in the Removal of Cesium by Soil Electrokinetic Remediation - Rudy Syah Putra; Alfi Ihda Amalia; Naila Zahrotul Jannah (Indonesian Journal of Chemistry, 2021)
The removal of cesium from artificially contaminated soil using electrokinetic remediation with nitric and acetic acid as electrolytes had been evaluated. In this study, uncontaminated soil was taken from four different sampling points (i.e., A, B, C, and D) in Kotagede, Yogyakarta, Indonesia. All samples were prepared as cesium contaminated soil (100 mg CsCl/kg soil), which have similar physicochemical characteristics with Fukushima soil, Japan. The electrokinetic remediation (EKR) was conducted using a graphite electrode in a constant voltage of 1.0 Vcm–1 for 7 days without electrolyte pH control, with 1.0 M nitric and acetic acid as electrolytes. The current profile during the EKR was recorded by a data logger for every 10 min. The remaining cesium in the soil was measured by a flame atomic absorption spectrophotometer at a wavelength of 852.1 nm. The results showed that the type of acid used in the experiments affected the removal of cesium. The highest cesium removal was achieved when nitric acid was used in the experiment and then followed by acetic acid. For all acids, the removal ability of cesium from soil was in the following order: soil C > soil A > soil D > soil B.